National Drug Policy - Musa, Mexhit (Technium BioChemMed, 2022)
The national drug policy is a professional and political document that defines the goals and priority tasks of the pharmaceutical sector, as well as the ways to achieve them. This document should form a framework for the development and operation of the pharmaceutical industry. The balance between all participants interested in the formation of this document, is the basis for the simultaneous harmonization of different interests and equal sharing of responsibilities. The necessity of developing a national drug policy arises from a number of determinants, which are reflected in the fact that: the drug saves lives, people can not predict the disease, drugs are complex chemical compounds and biologically active substances. People can not choose the right treatment without diagnosis and medical therapy, drugs are expensive, financial resources are always insufficient. The history of the National Medicines Policy (WHO) is relatively long: 1985. Conference of Experts on the Rational Use of Medicines in Nairobi (Kenya), 1987. Establishment of an Expert Working Group to Develop a Guide to National Medicines Policies, 1988 .publishing of a guide to BNPs, 1992. monitoring indicators of the national drug policy, 1995. the report of the committee of experts on the national drug policy was published. 2000. national drug policy monitoring indicators. 2002. published new guidelines for national drug policy. The national drug policy represents: Commitment to the goal and guidelines for action, should be a written document that contains the medium and long-term goals, priorities and strategies and key approaches to achieve them, provides a framework within which to coordinate the activities of The pharmaceutical sector, taking into account the public and private sector as well as all key actors in the pharmaceutical sector, should be developed systematically through the process of negotiation and harmonization of all interests. In a broader sense, national drug policy should promote equity and sustainability of the pharmaceutical sector, the main objectives of national drug policy are to ensure that drugs are effective, high quality, safe and relatively inexpensive, be not only present in the market, but also accessible to the population, in order to meet the needs of the entire population (essential medicines) and to ensure that medicines are used rationally. An integral part of the national drug policy process is the development of an action plan and work program for the development of the list of essential medicines. The essence of the concept of essential medicines is that the use of a limited number of carefully selected medicines, based on agreed therapeutic guidelines, leads to a better supply and lower costs, essential are those medicines that meet most of the needs for the health care of the majority of the population and therefore should always be available in the necessary dosage forms and at affordable prices. The essential drug list is a basic tool for drug management. The first WHO EDL (Essential Drug List) was published in 1977, and the last 15 were published in March 2007. The current WHO EDL (15th revision) contains 27 different therapeutic categories within which 388 drugs are distributed. (INN), with certain pharmaceutical qualities and forms. The drugs (INN) on the list are mainly representatives of the therapeutic-pharmacological groups, which gives the possibility that other drugs belonging to the same group, which are also effective, be included in the list as an alternative. The list of models is divided into main list and additional list. Drugs are listed INN, without being associated with specific brand names or manufacturers. The main list represents the minimum number of drugs that are needed for the health care system. It contains the most effective, safest and most economical drugs for priority diseases.